2015
DOI: 10.7860/jcdr/2015/11709.6000
|View full text |Cite
|
Sign up to set email alerts
|

AGE-Related Differences of Novel Atherosclerotic Risk Factors and Angiographic Profile Among Gujarati Acute Coronary Syndrome Patients

Abstract: Context: Although numerous risk factors have been established to predict the development of acute coronary syndrome (ACS), the risk factor profile may be different between the younger and older individuals. Aim:To analyse the frequency and pattern of atherogenic risk factors and angiographic profiles in age-stratified Gujarati patients with ACS. Materials and Methods:ACS patients undergoing coronary angiography at U.N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 10 publications
(20 reference statements)
7
46
0
4
Order By: Relevance
“…If the current trend continues, the burden of CAD in India will surpass other regions of the world by the year 2020 (5). In addition to higher rate, it is also reported that Indian individuals may develop CAD at a very early age (6). According to an estimate, more than half of death related to cardiovascular disease occurs in patients below the age of 50 years and one-fourth of acute myocardial infarction cases are being reported in patients under the age of 40 years (6).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…If the current trend continues, the burden of CAD in India will surpass other regions of the world by the year 2020 (5). In addition to higher rate, it is also reported that Indian individuals may develop CAD at a very early age (6). According to an estimate, more than half of death related to cardiovascular disease occurs in patients below the age of 50 years and one-fourth of acute myocardial infarction cases are being reported in patients under the age of 40 years (6).…”
Section: Introductionmentioning
confidence: 99%
“…According to an estimate, more than half of death related to cardiovascular disease occurs in patients below the age of 50 years and one-fourth of acute myocardial infarction cases are being reported in patients under the age of 40 years (6). It has also been noted that the clinical presentation, risk factor profile, and coronary anatomy of young patients who develop CAD differs to those who develops CAD at an older age (1,6,7). Overall, these studies have indicated that patients with early onset of CAD exhibit preponderance of singlevessel disease, and dominance of coronary risk factors such as hypercholesterolemia, family history of CAD, and cigarette smoking as compared to older patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Это согласуется с данными исследований, в которых многососудистое поражение было характерно для больных старших возрастных групп [14]. Также оказалось, что средний уровень ЛПНП в группе 2,3-сосудистого/поражения ствола ЛКА составил 3,5±1,4ммоль/л, а при однососуди-стом/незначимом поражении 2,9±1,0ммоль/л (p<0,001) (табл.…”
Section: материалы и методыunclassified